Survival of oral tongue cancer in low middle-income country: a cohort study - Ronika Devi Ukrani; Muhammad Hassan Danish; Mubasher Ikram; Karim Rizwan Nathani; Shaharyar Salim; Adnan Yar Muhammad; Shafquat Rozi; Nida Zahid; Haissan Iftikhar (The Egyptian Journal of Otolaryngology, 2023)
Abstract Introduction The incidence of oral tongue squamous cell carcinoma (OTSCC) is increasing. OTSCC is comparatively higher in our region owing to the consumption of tobacco, beetle nut, alcohol, and poor oral hygiene. There is paucity of survival data for OTSCC from our high-burden region. Background There is paucity of survival data for OTSCC from our high-burden region, we aimed to determine 5-year overall and disease-free survival of patients with OTSCC. Methods A retrospective chart review was conducted for all the patients treated for oral tongue squamous cell carcinoma from January 2000 and December 2013. The data on overall survival and disease-free survival was collected via telephonic interviews up till 2018. Kaplan Meier curves were plotted to graphically represent survival. Results A total of 131 patients were included. The mean age of the patients was 49.4 ± 12.98 years, with most patients being male (65.9%). The most common tumor stage was T2 (55.1%) and the most common nodal stage was N0 (57.7%). Five-year disease-free survival was 59.2%, and overall survival was 60.7%. Overall survival dropped steeply from 84.4 to 7.5% in patients who developed recurrence in our cohort. Conclusion The most significant factor influencing the survival of patients with OTSCC is tumor recurrence. 5-year recurrence-free survival was 84.4% which is greater than reported in literature. This could be due to the low incidence of perineural and perivascular invasion in our population. Further research on factors leading to recurrence should be done.